Meningkatkan Hasil Belajar PAK Melalui Metode Problem Beased Learning Fase B Kelas 4 SDN 005 Barong Tongkok - Natalina Natalina; Andarweni Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to improve the learning outcomes of Grade IV students in Phase B at SD Negeri 005 Barong Tongkok through the implementation of the Problem Based Learning (PBL) model on the topic of the Church Thanksgiving Prayer. The background of this research is the low student achievement in this subject, which is attributed to the lack of active student engagement during learning activities. The PBL model was chosen because it encourages students to think critically, collaborate, and find solutions to real-life problems that are relevant to their daily experiences. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation, learning outcome tests, and documentation. The results of the study showed that applying the PBL model can improve students' learning outcomes in terms of conceptual understanding, participation in discussions, and the ability to express the meaning of thanksgiving prayer contextually. Therefore, the PBL model is proven to be effective in enhancing student learning outcomes on the Church Thanksgiving Prayer material.